2015
DOI: 10.6061/clinics/2015(10)01
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled, crossover study in patients with mild and moderate asthma undergoing treatment with traditional Chinese acupuncture

Abstract: OBJECTIVES:This study sought to verify the effects of acupuncture as an adjuvant treatment for the control of asthma.METHODS:This was a randomized, controlled, crossover trial conducted at the Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo. A total of 74 patients with mild/moderate, persistent asthma were randomized into two therapeutic groups: Group A – 31 patients underwent 10 real weekly acupuncture sessions, followed by a 3-week washout period and 10 sham weekly acupuncture ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…The lung is close to the heart anatomically, so the two viscera have close association physio-pathologically. Based on the theory of Meridian-viscera Association and clinical practice, the Lung meridian and the Heart meridian are the commonly used meridians for pulmonary disorders including asthma [ 17 , 18 ]. Hence, this study will select Taiyuan (LU9), Lieque (LU7), and Chize (LU5) on the Lung meridian and Shenmen (HT7), Yinxi (HT6), and Shaohai (HT3) on the Heart meridian for the following reasons: (1) these acupoints have been proved to be effective in improving QoL and relieving symptoms of asthma patients [ 18 , 23 ], (2) all of these acupoints are specific acupoints on the two meridians, and (3) the selected acupoints are on the medial side of the upper arm and at the same nerve segment based on the modern anatomy so as to minimized the bias of comparison.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lung is close to the heart anatomically, so the two viscera have close association physio-pathologically. Based on the theory of Meridian-viscera Association and clinical practice, the Lung meridian and the Heart meridian are the commonly used meridians for pulmonary disorders including asthma [ 17 , 18 ]. Hence, this study will select Taiyuan (LU9), Lieque (LU7), and Chize (LU5) on the Lung meridian and Shenmen (HT7), Yinxi (HT6), and Shaohai (HT3) on the Heart meridian for the following reasons: (1) these acupoints have been proved to be effective in improving QoL and relieving symptoms of asthma patients [ 18 , 23 ], (2) all of these acupoints are specific acupoints on the two meridians, and (3) the selected acupoints are on the medial side of the upper arm and at the same nerve segment based on the modern anatomy so as to minimized the bias of comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture, as a main complementary and alternative therapy, has traditionally been used to control asthma in China for thousands of years. Recently, accumulating evidence has supported the benefit of acupuncture for asthma [ 17 , 18 ]. It is reported that acupuncture can significantly relieve the asthma-related symptoms, improve QoL, influence inflammatory cell counts [ 17 ], ameliorate of peak expiratory flow (PEF) variability [ 14 ], and increase the forced expiratory volume in 1 s (FEV1) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence indicates that acupuncture treatment can both significantly improve asthma-related quality of life (QoL) and lung function and decrease medication dosages for patients with asthma [5][6][7][8][9][10]. A recent meta-analysis including nine randomized controlled trials (RCTs) with a total of 777 patients demonstrated that the symptom response rate of conventional treatments plus acupuncture for asthma is statistically higher than that of conventional treatments alone [11].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence indicates that acupuncture treatment can both significantly improve asthmarelated quality of life (QoL) and lung function, and decrease medication dosages for asthmatic patients (5)(6)(7)(8)(9)(10). A recent meta-analysis, including nine randomized controlled trials (RCTs) with a total of 777 patients, demonstrated that the symptom response rate of conventional treatments plus acupuncture for asthma is statistically higher than conventional treatments alone (11).…”
mentioning
confidence: 99%